Comparison of the electromyographic activity patterns of elite rowers on the rowing ergometer and the Dyno - Schwaar, H.; Mattes, K. (World Congress of Performance Analysis of Sport VIII, 2008)
JANSHEN et al. (in press) have investigated the neuromuscular activation patterns of the lower extremities of seven male elite rowers, (sculling/ sweep rowing) during a simulated 2000m race on a rowing ergometer. They also recorded the myoelectric activity of the vastus lateralis, rectus femoris, biceps femoris, tibialis anterior and gastrocnemius lateralis by using a surface EMG. The collected data over two 30sec time slots, one minute resp. five minutes after the test started, showed similar activity patterns in regards to the sequence of activation. JANSHEN et al. (2006) also provided results concerning the analysis of the neuromuscular control during the bench pull. The electromyographic profiles of the arm-pull musculature revealed that the activation had ceased long before the dumbbell touched the bench. Due to the acceleration of the barbell masses, there was no need for the athletes to maintain the strength impulse until bench touch. MATTES (2005) also indicated the different exercise characteristics` of the bench pull and the Dyno, which is caused by a deviant resistance behaviour. For the purposes of strength training that emphasises in particular the maintenance of the strength impulse until the end of the drive phase the Dyno is may be preferred to the bench pull. Furthermore, it can successfully use to record the total arm-pull strength throughout the drive phase from start to finish for diagnostics. The main difference concerning the activity patterns between the ergometer and the Dyno results in the specific characteristics of the exertion of arms and legs during their movements. While the ergometer demands the interaction of arms and legs, the Dyno allows separate actions of both muscle groups. New potentials arise for a specific strength diagnosis of arms and legs. In addition, the results will be specified by the determination of an electromyographic profile of the rowing movement in a racing boat during on-water training in comparison to the movement on a rowing ergometer (cp. SOMMER et al. 2008).